Will human beings be superseded by generative pre-trained transformer 3 (GPT-3) in programming? - Muminov Ibrokhim Botir Ugli (International Journal on Orange Technologies, 2020)
In today’s world, which is full of innovations in various fields, the role of Information Technologies (IT) has increased substantially. Consequently, a mountainous number of independent software engineers as well as IT companies are working together in order to pave the way for the further developments in the IT world. There were a significant number of new technological advancements which have solved dozens of both virtual and real-world issues and have eased the burden from people’s shoulders. As a very conspicuous example would be Generative Pre-trained Transformer 3 or GPT-3 which was introduced in May 2020 as a part of a trend in natural language processing (NLP) systems of pre-trained language representations. This article will provide background data related to GPT-3, its applications in today’s world, positives and negatives, and the future of this remarkable, yet unpredictable tool.